THE IMPACT OF SERANG JAVANESE (JASENG) ACCENT ON ENGLISH PRONUNCIATION AT SMK PGRI 3 KOTA SERANG - Pratama, Alvin Rio; Qonaatun, Aa; Amalia, Lia (Journal of English Language Teaching and Literature (JELTL), 2023)
The objectives of this study are to identify the results of Serang Javanese students' pronunciation in English, the impact of Serang Javanese accent when speaking English and the difficulties Serang Javanese students face when speaking English. This research uses descriptive analysis method and qualitative approach. This research consists of 19 respondents, 14 male respondents and 5 female respondents. Data collection was conducted using four techniques namely observation, interview, pronunciation task, and documentation. This research uses data analysis and transcription techniques. The data analysis technique was carried out by processing transcripts of observation notes, interviews, pronunciation tasks, and document review. The data that has been obtained is then transcribed to explain the results of data collection. The findings of this study are that the pronunciation tasks of the two Serang Javanese-speaking students are very poor. The resulting impact is the sound produced by the Serang Javanese students becomes heavy and unpleasant to hear. Another impact is changing the meaning of the spoken word and making the listener misunderstand. The last impact is to make the listener confused. The Serang Javanese students have difficulties when speaking English, mainly due to the lack of vocabulary.